Exploring the social representations of vulnerable populations being helped - Bignone, Lisa (2022)
Resorting to Social Representation Theory, the aim of this study was to investigate the perceptions of help recipients about Help, namely in terms of the shared representations about Helping Institutions, the self-perceptions of aid recipients and the potential Social Status Distance with regard to their helpers. Twenty-five members of vulnerable groups that benefited from help programs offered by Non-Profit Institutions/Organizations, aged between 18 and 70-years-old, responded to semi-structured interviews. Following the theoretical-methodological orientation of the structural approach of Social Representation Theory (Abric, 1984), the 800 free evocations and 149 words produced during the interviews, underwent a prototypical analysis with open-EVOC software (2000). In addition to contributing to Social Representation Theory by considering the theme of helping relations, the results of the present study showed – in contrast to the literature on orientations toward help (Nadler, 1997; 1998; 2002; 2015) – the importance, at different levels, of both autonomy and dependency orientations (and not just the latter). This study showed the importance, for the recipients of help, of being protagonists, active and autonomous in the process of improving their psychological and material situation; together with the importance of enjoying material goods, even if it means depending on an institution. Results are discussed as a potential contribution to designing help programs that might provide greater benefits and well-being to help recipients.